2013
DOI: 10.1021/ja401553d
|View full text |Cite
|
Sign up to set email alerts
|

C–N Bond Cleavage of Anilines by a (Salen)ruthenium(VI) Nitrido Complex

Abstract: We report experimental and computational studies of the facile oxidative C-N bond cleavage of anilines by a (salen)ruthenium(VI) nitrido complex. We provide evidence that the initial step involves nucleophilic attack of aniline at the nitrido ligand of the ruthenium complex, which is followed by proton and electron transfer to afford a (salen)ruthenium(II) diazonium intermediate. This intermediate then undergoes unimolecular decomposition to generate benzene and N2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 32 publications
(30 reference statements)
2
21
0
Order By: Relevance
“…As such the reactivity with substrates is expected to take place on the doublet spin state only and the oxidants will react through single-state-reactivity [51,52] selectively. Mononuclear [53][54][55]. Indeed previous studies on mononuclear Ru IV =O complexes showed the high-spin states to be considerably higher in energy than the lower spin states [56] in agreement with what is seen here.…”
Section: Resultssupporting
confidence: 92%
“…As such the reactivity with substrates is expected to take place on the doublet spin state only and the oxidants will react through single-state-reactivity [51,52] selectively. Mononuclear [53][54][55]. Indeed previous studies on mononuclear Ru IV =O complexes showed the high-spin states to be considerably higher in energy than the lower spin states [56] in agreement with what is seen here.…”
Section: Resultssupporting
confidence: 92%
“…This complex is found to be highly electrophilic/oxidizing. For example, it readily undergoes C−N bond cleavage of aniline, C−H bond activation of alkanes, aziridination of alkenes, and functionalization of alkynes in non‐aqueous solvents.…”
Section: Figurementioning
confidence: 99%
“…Schiff-base (e.g. Salen) Ru-complexes enable versatile asymmetric catalysis for a range of chemical transformations, especially for carbene, nitrene, and oxene transfer reactions [11,146,215,216]. Complexes of this class reportedly serve as catalysts for oxidation/epoxidation, with chiral Ru-complexes such as Ru-porphyrin, desymmetric Ru-Schiff base and Ru-bisamide complexes being employed in asymmetric epoxidation.…”
Section: Ruthenium Complexes In Catalysismentioning
confidence: 99%